White Wine Antioxidant Metabolome: Definition and Dynamic Behavior during Aging on Lees in Oak Barrels - Rémy Romanet; Régis D. Gougeon; Maria Nikolantonaki (MDPI AG, 2023)
White wines' oxidative stability is related to a flow of chemical reactions involving a number of native wine compounds comprising their antioxidant metabolome. By applying the combination of powerful and modern analytical approaches (EPR, DPPH, and UPLC-qToF-MS-based metabolomics), we could define wine antioxidant metabolome as the sum of molecular antioxidant markers (AM) characterized by their radical scavenging (AM-RS) and nucleophilic (AM-Nu) properties. The impact of on-lees barrel aging of chardonnay wines on the antioxidant metabolome was studied for two consecutive vintages. The identification of wines' antioxidant metabolome allows for a detailed understanding of the transient chemical interplays involved in the antioxidant chemistry associated with well-known antioxidants and opens an avenue towards personalized winemaking. The present study gathers for the first time the dynamics of wines' antioxidant metabolome during on-lees aging. Monitoring the variations of the wine antioxidant metabolome can provide an avenue to better control the winemaking process using the knowledge of how to optimize the wine aging potential.